Preparation of Ru-Based Systems Through Metal Carbonyl Cluster Decomposition for the Base-Free 5-Hydroxymethylfurfural (HMF) Oxidation - Francesca Liuzzi; Francesco Di Renzo; Cristiana Cesari; Alice Mammi; Lorenzo Monti; Alessandro Allegri; Stefano Zacchini; Giuseppe Fornasari; Nikolaos Dimitratos; Stefania Albonetti (Molecules)
Metal carbonyl clusters, which can be seen as monodispersed and atomically defined nanoparticles stabilized by CO ligands, were used to prepare Ru-based catalysts with tuned basic properties to conduct the 5-hydroxymethylfurfural (HMF) aerobic oxidation to produce 2,5-furandicarboxylic acid (FDCA) in base-free conditions. The controlled decomposition of the carbonyl cluster [HRu3(CO)11]−, a methodology not yet applied to Ru catalysts for this reaction, on different supports focusing on controlling and tuning the basic properties of support allowed the formation of small Ru nanoparticles with a mean diameter of around 1 nm. The catalytic systems obtained resulted in more activity in the HMF oxidation than those prepared through a more common salt-impregnation technique, and the deposition of Ru nanoparticles on materials with basic functionalities has allowed avoiding the use of basic solutions in the reaction. The characterization by CO2-TPD of Mg(Al)O catalysts obtained from decomposition of layered double hydroxide hydrotalcites with different composition and activation has allowed disclosure of an important correlation between the selectivity of FDCA and the fraction of weak basic sites, which is decreased by the calcination treatment at increased temperature.